If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17(2b + 3) = 0 Reorder the terms: 17(3 + 2b) = 0 (3 * 17 + 2b * 17) = 0 (51 + 34b) = 0 Solving 51 + 34b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + 34b = 0 + -51 Combine like terms: 51 + -51 = 0 0 + 34b = 0 + -51 34b = 0 + -51 Combine like terms: 0 + -51 = -51 34b = -51 Divide each side by '34'. b = -1.5 Simplifying b = -1.5
| 5m+5=7m-7 | | (6y-3)5= | | 3x^3-13x^2+16=0 | | (2h-4)11= | | 3t^2+4t+1=0 | | 3(2+w)= | | g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= | | Y=Ax-Fx-C | | z^6-z^3-2=0 | | (12x-8)+3(2x-4)= | | 10x+3=3(2x+1)-x+8 | | -x+3+9x=-2+3x+10 | | -11c=89 | | 5=-3(x+2)-4 | | 6x+3+x=2+2x+21 | | 7x(4+4x)= | | 5x-4=2x+29 | | 5y=9 | | 0=9-5y | | 5x=-6 | | 10x=x+100 | | 6x+5=-2#-9 | | 4x^2-36x=-80 | | 6x+4x=65-3x | | 2+16/2+6=4 | | 3p^2-7p-6=0 |